Problems of Mastering 2/4; 3/4; 4/4 Measurements in Conducting - D. Raimova (International Journal on Orange Technologies, 2021)
This article is about the importance of schemes in mastering the technique of conducting. It is important to give the student an idea of the dimensions of the conductor's grid. Measurements have a simple and complex meter rhythm. The simple measure consists of one strong and one weak contribution. For these simple measurements - 2/2; 2/4; 2/8; 3/2; ¾; Includes 3/8 measurements. In complex measurements, there are two strong contributions and a weak contribution. -4/4 for complex measurements; 8/4; 9/4; 12/4 and so on Measurements are important in the process of mastering a work. This is convenient for the conductor and allows the team to better understand his wishes. The simpler, clearer, more concise, and more meaningful the basis, the more likely it is to convey the different requirements of the score using hand gestures, and the deeper the meaning of the conductor’s hand gestures. As mentioned above, there is information about the formation of strong and weak parts of a bar of any size.